2019
DOI: 10.33988/auvfd.615731
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content and in vitro digestibility of kermes oak (Quercus coccifera L.) growing in the provincial borders of Burdur

Abstract: The purpose of this study was to investigate the in vitro dry matter digestibility (IVDMD), nutrient content, cell wall components, total and condensed tannin content of kermes oak (Quercus coccifera L.) which is the main feed source for goat herds. Kermes oak was exemplified in 3 different stations during a year (12 months). Sampling was made to include leaves, some branches, acorns and young shoots, if any based on season, which were consumed by the goats. The amount of dry matter (DM), crude ash (CA), crude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In another study, it was found that the CF contents of kermes oak (124.2, 289.8, and 312.8 g/kg, respectively) were higher than those of the mock privet (116.0, 240.8 and 189.2 g/kg, respectively) in April, June, and September (Yolcu et al, 2014). In another study, the CF content in kermes oak was found to be within the range of 210.0-233.7 g (Türel and Buğdaycı, 2020).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In another study, it was found that the CF contents of kermes oak (124.2, 289.8, and 312.8 g/kg, respectively) were higher than those of the mock privet (116.0, 240.8 and 189.2 g/kg, respectively) in April, June, and September (Yolcu et al, 2014). In another study, the CF content in kermes oak was found to be within the range of 210.0-233.7 g (Türel and Buğdaycı, 2020).…”
Section: Resultsmentioning
confidence: 91%
“…Kökten et al (2012) found the CA contents in kermes oak and mock privet as 42.0 and 32.0 g/kg, respectively. On the other hand, Türel and Buğdaycı (2020) found the CA content to be 40.5 g/kg in the kermes oak. Whereas the amount of ME in the plant material is inversely associated with cell wall components, it has a positive association with CP and ash.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation